Spatial Spillover Effect and Spatial Distribution Characteristics of Transportation Infrastructure on Economic Growth: A Case of the Yangtze River Delta - Wang, Jian; Yang, Xuying; Qalati, Sikandar Ali; Deng, Yuzhou (Frontiers in Environmental Science, 2022)
As an important driving force for economic growth, transport infrastructure can effectively integrate regional resources, deepen regional cooperation, and promote the rational utilization of resources. The cross-regional connectivity of transport infrastructure makes its spatial spillover effect more prominent. In this paper, the entropy weight method is used to construct a comprehensive index reflecting the traffic infrastructure of 41 prefecture-level cities in the Yangtze River Delta, and the spatial distribution characteristics are analyzed. Based on three spatial weight matrices, the spatial Durbin optimization model is used to investigate the spatial effect of transportation infrastructure on economic growth in the Yangtze River Delta. The results show that regional transportation infrastructure and economic growth have significant spatial agglomeration characteristics and that the development of eastern cities is better. The transportation infrastructure of each city not only drives its own economic growth but also has a positive spatial spillover effect on the economic growth of adjacent areas. In order to achieve high-quality and integrated development in transportation, and to narrow the gap of transportation development in the Yangtze River Delta, we recommend that the spatial spillover effect of transportation infrastructure on economic construction should be given full consideration.